Development of IoT-based Health Monitoring System using Blynk - Chiew Hong, Wong; Siong Seng, Yee; Mior Idris, Wan Nur Arifah; Chee Yee, Tang; Hui Mun, Teoh; Tukiran, Zarina (Evolution of Information, Communication and Computing System, 2022)
The leading cause of death in Malaysia is heart disease. According to the data of the World Health Organization (WHO) published in May 2014, the rate of coronary heart disease deaths in Malaysia has reached 23.10% of total deaths [1]. The Department of Statistic Malaysia stated that the statistic of death caused by heart disease in Malaysia was 13.9% which higher than the death caused by accident [2]. Heart disease occurs when the abnormalities level of fats (lipids) accumulates to forms plague in a coronary artery and narrowing the arteries. At the same time, it reduce the oxygen-rich blood flow to the heart and leads to heart attack, stroke or even death [3]. The most common sign of coronary artery diseases is chest pain or angina which caused discomfort, heaviness, and pressure in the chest [4]. The other symptoms included shortness of breath, palpitations or irregular heartbeats and faster heartbeat [5]. Furthermore, the common risk factors of heart disease are high Body Mass Index (BMI), obesity, diabetes, smoking, and high blood pressure. Heart diseases are often thought to be an adult person’s problem but it can happen to anyone regardless of gender and age [6].